Youth associations and cooperatives: Getting young people into work - Alexandra Löwe; Susan Njambi-Szlapka; Sanyu Phiona (Overseas Development Institute (ODI), 2019)
The Youth Empowerment Through Agriculture (YETA) programme, in partnership with the Mastercard Foundation, addresses the employment challenges faced by young people in mid-Western and Northern Uganda through the support and formation of youth associations. This report aims to understand how these associations can address the challenges typically faced by underemployed or unemployed youth and to capture the lessons learned by the programme. The overarching question discussed in this study is how collective action can help address the challenges that young people cannot overcome individually. Young people occupy a unique position by virtue of being in transition from childhood to adulthood. This means that they can no longer rely on their parents to support them, but nor do they have the social, economic and political resources associated with adulthood. There is a long history of collective action in rural communities with the aim of providing excluded groups with the networks necessary to access such resources. However, their application to youth employment challenges and the specific forms of exclusion experienced by young people is comparatively new. This report seeks to understand their operation in such contexts. It also looks in depth at the ways in which collective action can help to address young people's exclusion from financial services and how they can build realistic and actionable aspirations.
Keywords: 330